Pemanfaatan Media Audio Visual Terhadap Hasil Belajar Keterampilan Menyimak Kelas MI Nur Arrahman Kajuara - Riska Safitri; Khaeruddin Kiramang (JURNAL MAPPESONA, 2025)
This study was conducted with the aim of:indentifying and assessing the use of audio-visual media on the results of listening skills,namely in carrying out the teaching and learning process,learning media is very necessary so that students can be more active in learning data collection methods,namely starting with observation,interviews,and documentation. The data were processed using observation techniques,interviews,questionnaires and documentation,as well as testing the validity of the data in this study using sociological techniques and pedagogic techniques.The results og the analysis of the data obtained show that student learning outcomes for listening skills still need to be improved,it is proven that when in the question and answer learning process there are only a few students who raise their hands and especially in reading children get bored quickly